AN ANALYSIS OF THE TRANSLATION OF THE IDIOMS IN AGATA CHRISTIE’S Mrs. Mc GINTY’S DEAD INTO INDONESIAN IN BUDIYANTO PRAMONO’S Mrs. Mc GINTY SUDAH MATI - Albertus Suwardi (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2013)
Idiom is a number of words which are joined together means iri.something different from the meaning of the words when they stand alone. In order to reproduce the closest natural equivalent in terms of the source context, a translator normally attempts to make adjustments in idioms due to a literal translation of idioms into another language will not make sense.This paper is mainly aimed at finding out how a translator can translate and discover the natural equivalent of English idiomatic expression. The findings show that there are two types of adjustments that are used in translating the idioms. First, by non figurative expression equivalent and second, by figurative expression equivalent.